The ancient languages of Asia and the Americas - Woodard, Roger D.; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
This book, derived from the acclaimed Cambridge Encyclopedia of the World's Ancient Languages, describes the ancient languages of Asia and the Americas, for the convenience of students and specialists working in that area. Each chapter of the work focuses on an individual language or, in some instances, a set of closely related varieties of a language. Providing a full descriptive presentation, each of these chapters examines the writing system(s), phonology, morphology, syntax and lexicon of that language, and places the language within its proper linguistic and historical context. The volume brings together an international array of scholars, each a leading specialist in ancient language study. While designed primarily for scholars and students of linguistics, this work will prove invaluable to all whose studies take them into the realm of ancient language.
Languge in ancient Asia and the Americas : an introduction / Roger D. Woodard -- Sanskrit / Stephanie W. Jamison -- Middle Indic / Stephanie W. Jamison -- Old Tamil / Sanford B. Steever -- Old Persian / Rüdiger Schmitt -- Avestan / Mark Hale -- Pahlavi / Mark Hale -- Ancient Chinese / Alain Peyraube -- Mayan / Victoria R. Bricker -- Epi-Olmec (Zapotec appendix) / Terrence Kaufman and John Justeson -- Appendix 1. Reconstructed ancient languages / Don Ringe -- Appendix 2. Full tables of contents from The Cambridge encyclopedia of the world's ancient languages, and from the other volumes in the paperback series.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Extinct languages -- Asia; Extinct languages -- America; Asia -- Languages; America -- Languages; Electronic books